ETCHING OF DIAMOND CRYSTALS IN THE SYSTEM SILICATE MELT-C-O-H-S FLUID UNDER A HIGH PRESSURE - Sonin V.M.; Afanas'ev V.P.; Tomilenko A.A.; Zhimulev E.I.; Chepurov A.I. (My University, 2003)
This paper presents experimental data on etching plane-faced octahedral diamond crystals in the system silicate melt-C-O-H-S fluid at 3 GPa and 1300°C. It was established that the curved-surface crystals of octahedroid type with micromorphological features characteristic of natural diamonds are formed from plane-faced individuals during etching. The introduction of sulfur into the system does not change the morphology of etched diamond in comparison with the etching results in the system silicate melt-C-O-H fluid. The contact of sulfide melt droplets with diamond crystal surface gives rise to the formation of faced cavities owing to the higher carbon solubility in sulfide melt compared to that in the silicate liquid.